2022
DOI: 10.1097/olq.0000000000001734
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Demographic Features of 49 Patients With Human Monkeypox Virus–Confirmed Infection in a Tertiary Care Center in Valencia, Spain: A Descriptive Study

Abstract: This was a study of monkeypox-infected patients in a tertiary care center in Spain describing the epidemiologic, clinical, and microbiologic features of 49 patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(55 citation statements)
references
References 19 publications
1
52
0
Order By: Relevance
“…However, majority of the studies on pre‐2022 outbreaks have documented animals as the primary source of monkeypox virus transmission and human‐to‐human cases were rare. During the 2022‐outbreak we detect that majority of the cases (100%) were human‐to‐human transmitted 9,11,13–16,18,21,24,29 . These epidemiological changes are probably the result of genetic changes of the virus and origin of strains with altered properties and changes in human behaviors.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…However, majority of the studies on pre‐2022 outbreaks have documented animals as the primary source of monkeypox virus transmission and human‐to‐human cases were rare. During the 2022‐outbreak we detect that majority of the cases (100%) were human‐to‐human transmitted 9,11,13–16,18,21,24,29 . These epidemiological changes are probably the result of genetic changes of the virus and origin of strains with altered properties and changes in human behaviors.…”
Section: Discussionmentioning
confidence: 96%
“…Age Numerous studies have documented that higher frequency of monkeypox virus infection in people of specific age groups. 4,8,9,11,15,[18][19][20][21][22][23]25,[28][29][30][31] Sex Most of the recent published studies found that men are the major group infected by monkeypox virus during 2022 outbreak. 4,8,9,11,15,[18][19][20][21][22][23]25,[28][29][30][31] Ethnicity People of diverse races were infected during this outbreak.…”
Section: Risk Factors Referencesmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] Previous studies described lesions as pustules or pseudopustules without content, 1,2 but they are actually thickroofed vesicles. 3 Histopathologic studies have shown the cutaneous lesions characterized by ballooning degeneration of basal keratinocytes and spongiosis of a mildly acanthotic epidermis progressing to full-thickness necrosis of a markedly acanthotic epidermis containing few viable keratinocytes. [4][5][6] We have performed a biopsy of an initial lesion.…”
Section: Discussionmentioning
confidence: 99%
“…Human mpox virus, a zoonosis first recognized in Africa, has recently increased exponentially in Europe and United States with a prevalent sexual transmission mainly affecting men who have sex with men. [1][2][3] Clinical manifestations include prodromes of malaise and fever. After 1-5 days of infection, the development of cutaneous lesions that evolve through different stages, beginning as papules and vesicles that turn into umbilicated pustules that eventually ulcerate, leading to a characteristic central necrotic crust.…”
Section: Introductionmentioning
confidence: 99%